GRADE IT—A Literacy-Based Assessment Tool for Generating Research-Based Assessment Data to Evidence the ImpacT of Anti-doping Education via Athletes' Capability to Make the Right Decision - Blank, Cornelia; Gatterer, Katharina; Overbye, Marie; Schobersberger, Wolfgang; Streicher, Bernhard; Petróczi, Andrea (Frontiers in Sports and Active Living, 2022)
The International Standard for Education (ISE) mandates Code Signatories to plan, deliver, and evaluate anti-doping education. Performance-based evaluation of anti-doping education requires alignment between educational goals, content, and defined outcomes. Based on an existentialist teaching and learning philosophy, we aimed to develop and test an anti-doping impact evaluation tool, to assess the impact of anti-doping education on doping awareness, literacy (DAL), perceived trustworthiness, and legitimacy. We propose that the impact of anti-doping education is best captured through assessment of situation-specific (social) cognitive mediators of actions that influence athletes’ choices in the context of sport-related goals. In phase one, we aimed to develop and test the Generating Research-based Assessment Data to Evidence the ImpacT of anti-doping education (GRADE IT) evaluation tool that comprised a set of social cognitive components: anti-doping knowledge, DAL, perceived trustworthiness, and legitimacy of anti-doping (organizations). In phase two we assessed whether anti-doping education impacts knowledge, the three DAL stages (functional, interactive, and critical literacy), perceived trustworthiness and legitimacy. Phase one enrolled 986 junior elite athletes, and we showed that all GRADE IT components performed well. After revision of the tool for phase two, we validated the assumption that anti-doping education impacts the likelihood that athletes will make the ‘right’ choice (based on a new set of data from 1255 junior elite athletes). Comprehensive education was associated with higher scores for all stages of DAL, as well as perceived trustworthiness and legitimacy. Even athletes reporting no education had positive scores for all included outcomes, supporting the assumption that most athletes wish to engage in clean sport behaviors and might need anti-doping education not to prevent them from doping, but rather to reinforce their commitment to clean sport. In conclusion, GRADE IT, which is available in 23 languages, is a suitable tool for application to young, emerging athletes to satisfy the ISE requirement for evaluating anti-doping education programs. Researchers and practitioners alike are advised to collect additional data to further validate the tool for adult athletes, and to apply it longitudinally to identify if changes in doping prevention policies have a delayed effect on DAL, perceived trustworthiness, and legitimacy.